Exploiting Multicomponent Polymerisations for Non-Viral Gene Delivery - O'Shaughnessy, Lewis (2025)
RNA is a powerful therapeutic technology, with the potential to treat many conventionally “undruggable” diseases, however, RNA needs a vector to enter cells. Cationic polymers offer one effective vector technology, which could provide a scalable and highly adaptable platform for RNA delivery. However, polymeric vectors are yet to make it to the clinic and lipid nanoparticles are currently the most commonly used vector in clinical settings. The development of novel families of highly functionalised polycations could provide a new range of vectors that efficiently deliver RNA without the immunogenicity of lipid nanoparticles and target a wider range of tissue types. Multicomponent reactions (MCRs) provide a means to efficiently synthesise highly functionalised molecules by combining multiple functional groups in just one step. This work used two MCRs, the Passerini 3-component reaction (P3CR) and the Ugi 4-component reaction (U4CR), for the synthesis of novel polycationic biomaterials for RNA delivery. The flexibility of these reactions, and the inherent biodegradability of the products offers much potential for the development of complex products with good cytocompatibility. In Chapter 2, a family of novel polycations were synthesised directly from the P3CR, which was used to combine bifunctional monomers via a step growth polymerisation method. A small polymer library was developed and further broadened by the use of click-reactions for polymer post-functionalisation. Following investigations in 2D cell culture the polymers were found to be non-cytotoxic, although they did not efficiently deliver RNA to cells. However, they did display an unusual, intrinsic luminescent behaviour on incubation with cells. Work in Chapter 3 instead utilised the P3CR as a post-functionalisation technique for end-capping of poly(beta-amino ester)s (PBAEs). PBAEs are a widely studied polymeric vector, with good cytocompatibility and transfection efficiency, the end-caps of various PBAEs have been found to have a significant impact on their properties and transfection capability. By employing the P3CR as an end-capping procedure it was possible to synthesise a family of novel polymers by incorporating different aldehyde and isocyanide components into the end groups of an acid terminated PBAE. The materials were then tested for RNA delivery and cytocompatibility with model RNAs across different cell lines. Many of the polymers were found to outperform the amine terminated PBAE control, without increasing cytotoxicity. Under certain conditions, transfection efficiency for select polymers was even found to match or exceed that of Lipofectamine, a commercial transfection agent. Finally, in Chapter 4, a range of the same diacid monomers developed in Chapter 2 were also applied to the U4CR, which was also used as a direct step growth polymerisation technique, in this instance by combining the diacids with diamines alongside aldehydes and isocyanides. Again, a small polymer library was synthesised by this technique and screened for transfection efficiency with mRNA. Whilst many of the polymers showed little to no transfection capability, several of the polymers delivered significant amounts of RNA. However, those polymers that induced the greatest protein expression were also found to be cytotoxic. Different formulations and RNA doses were trialled to mitigate this, but no conditions were found that reduced toxicity without also reducing transfection efficiency. Overall, this work amounts to the development of entirely new polymer families synthesised from direct multicomponent polymerisations: the first polycations synthesised by Passerini 3-component polymerisation; and the first Ugi 4-component reaction derived polymers used for RNA delivery. In addition, this work also reports, the first recorded use of the P3CR for modification of PBAEs, which was found to enhance their capacity for RNA delivery. These materials provide a foundation for future research and demonstrate that these isocyanide-based MCRs provide flexible and efficient synthetic tools for future polymer synthesis.